Goods and Service Tax in India and Its Impact on International Trade (With Special Reference to Indo-US Trade Relation) - Sharma, Prerna; Kumar, Neeraj (Journal of Commerce and Trade, 2019)
India has the seventh largest economy of the world. The main factor for any economy that leads to growth of the country’s economy is international trade. So by the reform in the indirect taxation system, it becomes a vital part to understand its impact on international trade performance. Multiple indirect taxes are replaced by the GST which were earlier imposed on export and import and will work as a single consolidated tax. This reform will bring a lot of changes for the economy and international trade as well. It also includes the significant impact on the international trade as IGST Act shall be applicable to the import and export and many of the exemptions associated with various taxes for exporters will be abolished. As trading between India and US has developed a very strong relationship in the few last years, so it is quite obvious that after this indirect taxation reform, INDO-US trade relationship will also get affected. The purpose of this study is to find that how international trade & services will be affected by the implementation of GST. And as it is observed from the last decade that India and US are playing a leading partner role so will this exercise be repeated in next upcoming years? This study will help to find the opportunities with its challenges. Classification-JEL : F 23, K 10, K 23.